Semi-automatic building footprint using multirotor and fixed wing UAV - Nabila Ismail; Khairul Nizam Tahar (Institute of Advanced Engineering and Science, 2020)
The current techniques to extract building footprints frequently involve Light Detection and Ranging (LiDAR), as well as satellite images. The UAV is proposed to acquire aerial imagery in this study as it is more efficient, time-efficient, and inexpensive, especially for small budget projects. Hence, this study evaluated the building footprints from different UAV platforms. The objectives of this study are to perform the different UAV image processing of building footprints using fixed-wing UAV and multi-rotor UAV, as well as to analyse the outcomes of building footprints from different UAV platforms with existing layout plans. The methodology begins with a preliminary study, and continued with acquisition of data via UAV, data processing, and lastly, analyses of the outcome from different platforms. Based on the analysis in terms of area, the accuracy gained by using multi rotor UAV had been better than that for fixed wing UAV with area difference of 13.648 m² compared to 18.091 m². Lastly, it can be summarised that the area displayed better results with multi rotor UAV, in comparison to the area obtained by using fixed wing UAV. Thus, it is recommended for future studies to use other UAV platforms and other methods for extraction of building footprints, such as orthoimages and digital elevation model.